A model of pentaquarks - D. Germani; F. Niliani; A. D. Polosa (European Physical Journal C: Particles and Fields, 2024)
Abstract We describe pentaquarks as ‘baryo-charmonia’ with a color octet $$c{\bar{c}}$$ c c ¯ core bonded to a color octet three-quark system. Fermi statistics of the light quark cloud allows to describe two pentaquark triplets: a lower one, well supported by experiment, and a higher one with strangeness. For the time being, the lowest line of the strange triplet has been experimentally identified in a $$3σ $$ 3 σ peak. Data also suggest two different production mechanisms for pentaquarks. We show how this can be described in the proposed scheme.